How can we prove that a preventive measure in elite sport is effective when the prevalence of the injury (eg, ACL tear in alpine ski racing) is low? A case for surrogate outcomes - Kröll, J.; Spörri, J.; Elspeth Steenstrup, S.; Schwameder, H.; Müller, E.; Bahr, R. (British Journal of Sports Medicine, 2017)
When dealing with small cohorts, as is typical in elite sport, the well-known fourstep `sequence of prevention` described by van Mechelen et al potentially represents a vicious circle: When introducing a prevention measure, an otherwise reasonable call for targeting specific subgroups (ie, relevant groups of athletes, injury locations and specific injury causes) may undermine study power, breaking down an already-small baseline cohort into undersized pieces. Consequently, statistical testing becomes impossible. To illustrate the problem we discuss a recently implemented preventive measure in alpine ski racing as an example, highlight the influence of sample size and effect size on study power and the possibility for statistical hypothesis testing and provide a solution to increase study power for comparable injury prevention initiatives in elite sports.